Eastern Spiritual Traditions Through the Lens of Modern Scientific Worldview - Tetiana V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. This paper aims to analyze Eastern spiritual traditions in the context of modern scientific worldview. Methodology. The author has used hermeneutical methodology, along with integrative approach. Theoretical basis and results. Modern perception of the world is undergoing drastic changes: it shifts towards plurality, temporality, and complexity. Increasingly, people feel that their familiar world of order and stability gives way to chaotic, unpredictable world, which exists under its own rules. Old scientific theories, ideologies, and values are destroyed. This leads to awareness of imbalance, ambiguity of human existence and, thus, to the new explanation and understanding of reality. Today the universe is perceived through the lens of syncretism: it is impossible to separate human from nature, consciousness from matter, subject from object. Humanity faces such a chaotic, uncertain worldview not for the first time. Duality and attempts to overcome it permeate the entire history: from traditional archaic cultures to modern civilized societies. M. Foucault, J. Derrida, R. Barthes, U. Eco, G. Deleuze, J.-F.Lyotard urged to abandon dogmatism, monologue perception and explanation, interpretation based on binary oppositions. The world, which is necessary to reach, occurs to be Nothing, Nothingness. In this world, people are seeking for reality regardless of any rules, regulations, notions, and concepts. Here artificial constructs of the human mind, such as Material – Ideal, Determinism - Indeterminism, Finiteness - Infinity, Necessity – Randomness, are united. Trying to reconcile continuity of being with discreteness of consciousness, they appeal to Eastern mystical teachings, in particular, to Zen Buddhism. The core concept of this school is also based on the unity of all things and the idea of the singularity of the world. The main goal of Eastern mystical traditions is to achieve the state of absolute unity through meditative techniques that have been mastered over centuries. Meditation acts as a means of overcoming binary oppositions inherent to any given culture. It contributes to the experience of one absolute unity of all existence. Scientific novelty. Modern science reaffirmed one of the basic statements of Eastern mysticism: our concepts that we use to explain the world (such as past, present, future, physical space, personality, etc.) are not fundamental characteristics of reality. They are products of thinking, that is, they are the map rather than the territory. Conclusion. In contrast to Western paradigm, the main characteristic of Eastern philosophy and science is the non-mathematical, non-technical approach to an understanding of the universe. Eastern sage has never separated himself from the Nature. He has experienced all phenomena in the world as manifestations of a basic Oneness, Wholeness, as the various aspects of spiritual unity.